Application of an Intestinal Spatula in Optimizing a Sacrospinous Ligament Suspension - Zhu X; Chen Y; Song Y; Liang M; Ran G; Chen C (International Journal of Women's Health, 2025)
Xiaofan Zhu, Yingfan Chen, Yao Song, Miao Liang, Guangqin Ran, Cheng Chen Department of Gynaecology and Obstetrics, Chongqing General Hospital, Chongqing University, Chongqing, 401147, People’s Republic of ChinaCorrespondence: Cheng Chen, Department of Gynaecology and Obstetrics, Chongqing General Hospital, Chongqing University, No. 118, Xingguang Avenue, Liangjiang New Area, Chongqing, 401147, People’s Republic of China, Email chencheng961@126.comObjective: The purpose of this study was to investigate the application of an intestinal spatula in a sacrospinous ligament suspension, the effects of this surgical method on the surgical field, and surgical effectiveness.Methods: The clinical data of 33 patients who underwent suspension using intestinal spatula and 33 patients who underwent traditional surgery were collected, and the duration of surgery, amount of intraoperative blood loss, degree of postoperative pain, and degree of preoperative and postoperative uterine prolapse between the two groups were compared.Results: Multivariate analysis revealed that the modified technique significantly reduced anal pain incidence (OR=0.17, P=0.015) and improved anatomical C-point recovery (β=− 0.73, P< 0.001), though no significant differences were observed in operative time or blood loss.Conclusion: This study revealed that the application of an intestinal spatula in a sacrospinous ligament suspension can improve the surgical effect and reduce the incidence of postoperative complications, which is of clinical significance.Keywords: intestinal spatula, sacrospinous ligament suspension, surgical field, surgical effectiveness